COMPARATIVE CONTROLLED STUDY OF ANTIHYPERTENSIVE EFFICACY AND SAFETY OF CARVEDILOL IN PATIENTS WITH HYPERTENSION AND OBESITY OR DIABETES 2 TYPE (BASED ON RESULTS OF MULTICENTER TRIAL ACCORD) - Yu. V. Yu.V. Lukina; S. Yu. Martsevich; A. D. Deev; S. A. Shalnova (Рациональная фармакотерапия в кардиологии)
Aim. To study efficacy and safety of beta-blocker with vasodilating properties carvedilol (Acridilole, Akrihin, Russia) as a part of the combined therapy of patients with arterial hypertension (HT) and diabetes mellitus 2 type (DM2) and/or obesity.Material and methods. 592 patients: 176 men (29,7%) and 416 women (70,3%) with HT were examined. 194 patients had D2 and 398 patients had obesity. Patients were randomized for carvedilol therapy (n=291) or control group (n=301). Carvedilol was prescribed additionally to current therapy in dose of 6,25 mg BID, in 2 weeks the dose was increased to 12,5 mg BID if it was necessary. Blood pressure (BP) and heart rate, number of angina attacks were registered at visits. ECG, laboratory analysis (plasma lipide profile, serum glucose, glycolised haemoglobin, serum K+ and Na+), evaluation of depression and anxiety status (according to special questionnaires) were performed on the first and the last visits.Results. 582 patients completed the study. 7 patients dropped out from carvedilol group and 3 patients - from control group. The levels of systolic BP (SBP) and diastolic BP (DBP) were decreased during study, more significantly in carvedilol group (р<0,0001). SBP decreased on 24,8 mm Hg in patients of carvedilol group and on 21,4 mm Hg in patients of control group. DBP decreased on 12,5 mm Hg and 11 mm Hg respectively. Angina attacks were registered less often in patients of carvedilol group (р=0,001). Serum glucose and lipid spectrum did not change in both groups. Depression level decreased in patients receiving carvedilol. 17 side effects were registered in carvedilol group and 15 - in control group (р=0,575)Conclusion. High antihypertensive efficacy of carvedilol is confirmed in hypertensive patients with DM2 and/or obesity. Good tolerability and metabolic neutrality of carvedilol is also observed.